An unusual benzoisoquinoline-9-one derivative and other related compounds with antiproliferative activity from Hawaiian endophytic fungus Peyronellaea sp. FT431 - Li, Chun-shun (2019)
Fil: Fil: Li, Chun-shun. University of Hawai'i at Hilo. Inouye College of Pharmacy. Department of Pharmaceutical Sciences; United States.